(untitled) (Eurasian Research Bulletin, 2023)
Significant increase in interest due to the following factors: want to describe the global perspective of diverse language speakers; requirement to discover universal aspects of language material. Improvements should be made to bilingual dictionaries so that group, social, gender, age, and other linguistic characteristics are described, as well as nationalspecific features of semantics translated conformity. There is also a need to increase interest in national semantic specificity and study national specificity of language thinking. Based on examples from four different languages, the paper considers a solution to the theoretical and practical issues of lacunarity that are related to language comparison. It demonstrates the falsity of some data and the need to distinguish between lacuna and lacunar units, as well as between inter-linguistic and lacunas and lacunar units (and their types). It has been demonstrated that the lacunas in the universal paradigm represent the uniques of the universal.